Clinical profile of periodic paralysis - Khan, NA; Khan, AU; Hasan, MI; Dhatta, PK; Rahman, MW; Akter, M; Rahman, S; Ferdous, J; Miah, AK; Sarker, CB (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):28-33 The abstract of this article is available on the PubMed website